Matrix Methods of Structural Analysis - Nagarajan, Praveen; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This book deals with matrix methods of structural analysis for linearly elastic framed structures. It starts with background of matrix analysis of structures followed by procedure to develop force-displacement relation for a given structure using flexibility and stiffness coefficients. The remaining text deals with the analysis of framed structures using flexibility, stiffness and direct stiffness methods. Simple programs using MATLAB for the analysis of structures are included in the appendix.Key Features Explores matrix methods of structural analysis for linearly elastic framed structures Introduces key concepts in the development of stiffness and flexibility matrices Discusses concepts like action and redundant coordinates (in flexibility method) and active and restrained coordinates (in stiffness method) Helps reader understand the background behind the structural analysis programs Contains solved examples and MATLAB codes.
1. Introduction -- 2. Flexibility and Stiffness: Characteristics of Structures -- 3. Flexibility Method -- 4. Stiffness Method -- 5. Direct Stiffness Method
Includes bibliographical references and index.
Also available in print format.
Keywords: Structural analysis (Engineering) -- Matrix methods; TECHNOLOGY & ENGINEERING / Structural; Electronic books